2023
DOI: 10.1177/20552076221149294
|View full text |Cite
|
Sign up to set email alerts
|

An online mental health informed physical activity intervention for emergency service workers and their families: A stepped-wedge trial

Abstract: Objective Emergency service workers are at risk of experiencing poor mental health due to repeated exposure to potentially traumatic events. Promoting healthy lifestyle factors may help improve health outcomes and quality of life among this population. This study aimed to evaluate the efficacy of a 10-week physical activity (PA) and diet programme delivered via Facebook for sedentary emergency service workers and their support partners on levels of psychological distress. Methods We delivered a 10-week interve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…In line with this, research by Moreira et al (2022) indicated that online workplace exercise programs also have positive impacts, leading to better physical function, enhanced performance, and improved quality of life. Additionally, online lifestyle interventions have proven effective in reducing psychological stress, which is associated with improvements in various health outcomes for employees [26]. Interventions that leverage digital platforms for physical exercise have proven to be suitable for meeting physical activity (PA) recommendations within specific populations [27].…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, research by Moreira et al (2022) indicated that online workplace exercise programs also have positive impacts, leading to better physical function, enhanced performance, and improved quality of life. Additionally, online lifestyle interventions have proven effective in reducing psychological stress, which is associated with improvements in various health outcomes for employees [26]. Interventions that leverage digital platforms for physical exercise have proven to be suitable for meeting physical activity (PA) recommendations within specific populations [27].…”
Section: Introductionmentioning
confidence: 99%